The sliding wear of UHMWPE against ceramics in solutions containing proteins - Kernick, Melissa Jane (Centre for Materials Engineering, 2017)
The sliding wear behaviour of ultrahigh molecular weight polyethylene (UHMWPE) sliding against partially stabilised zirconia (PSZ) and alumina ceramic counterfaces in various lubricating media was investigated. Wear tests were conducted in order to investigate the effect that the addition of proteins to the lubricating solutions had on the wear behaviour of the UHMWPE against a smooth counterface of PSZ . The lubricants selected were physiological saline solution, distilled water and physiological saline solution containing small additions of synovial fluid and up to 15'% by volume of albumen solution. The effect of the addition of proteins to the lubricating solutions on the production of wear debris was also studied. ii The effect of changing the counterface roughness from Ra of 0.01 μm to 0.06μm was also investigated. The wear behaviour of UHMWPE against alumina ceramics in distilled water was compared to that of UHMWPE against PSZ in similar conditions.